Analisis Komparatif Ekonomi Islam, Kapitalisme, dan Sosialisme dalam Merespons Disrupsi Kecerdasan Buatan: Perspektif Maqashid As-Syariah - Yaskur Yaskur; Ichsan Iqbal (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
The disruption of Artificial Intelligence (AI) exacerbates the structural weaknesses of capitalism (extreme inequality) and socialism (inefficiency and incentive crisis). This study comparatively analyzes the responses of capitalism, socialism, and Islamic economics to AI disruption, employing Maqasid al-Shariah as an evaluative framework. Using a qualitative, literature-based approach, data were drawn from primary sources (Smith, Marx, Chapra, Auda) and reputable journal articles, and analyzed through content analysis and the comparative method of Miles, Huberman, and Saldana. The five pillars of Maqasid are operationalized through Auda’s systems approach, which is multidimensional, holistic, and purpose-oriented. The findings reveal that capitalism fosters market efficiency yet generates digital monopolies and surveillance capitalism; socialism offers precision centralized planning but risks digital authoritarianism; whereas Islamic economics positions AI as an instrument of trusteeship (khalifah) to realize human development and distributive justice by optimizing digital ZISWAF (zakat, infaq, sadaqah, and waqf). The novelty of this study lies in deploying Maqasid as a dynamic, systemic analytical tool rather than a merely normative doctrine. In conclusion, Islamic economics transcends the market-versus-state dichotomy by integrating technological innovation and spiritual welfare (maslahah). A limitation of the study is its theoretical-conceptual nature, which calls for further empirical research.